Infografis Sebagai Media Komunikasi Preventif Puskesmas 2 Purwokerto Utara Dalam Pengendalian Gula, Garam dan Lemak Bagi Remaja - Prita Suci Nurcandrani Suci Nurcandrani; Rizki Ardhi Rahman; Merliana Nur Khasidah (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
The 2018 Basic Health Research noted that stroke sufferers had increased over the past five years, from 7% to 10.9%. Stroke begins with excessive consumption of sugar, salt and fat (GGL). The government is working to prevent stroke starting from the indicated age of being potentially threatened with the disease, namely adolescents aged 13 to 18 years. The excessive content of GGL is found in junk food which is usually consumed by teenagers. Puskesmas Purwokerto Utara 2 wants a digital information media to intervene in these prevention activities. The output of this activity is an infographic aimed at adolescents which contains the importance of a healthy lifestyle by not consuming excessive junk food. The method used is the socialization of the use of the infographics to the health promotion division of the puskesmas, school health businesses located in the working area of the puskesmas, and adolescents who are considered influential in their communities as agents of change.